Risk factors and mortality for patients with Bloodstream infections of Klebsiella pneumoniae during 2014-2018: Clinical impact of carbapenem resistance in a large tertiary hospital of China - Haiyan Chang; Jie Wei; Wanqing Zhou; Xiaomin Yan; Xiaoli Cao; Lingyun Zuo; Shixing Chen; Kefang Yao; Rui Huang; Yuxin Chen; Chao Wu (Elsevier, 2020)
Background: Bloodstream infection (BSI) caused by Klebsiella pneumoniae (KP), especially carbapenem-resistant KP (CRKP), results in high morbidity and mortality. Aims: We aim to identify risk factors that associated with the mortality of patients with KP BSI, as well as predictors of developing CRKP BSI. Results: In this retrospective cohort study, we examined 285 inpatients with BSI caused by KP in a tertiary hospital in China between 2014 and 2018, and 46 patients were infected with CRKP. We identified that hematological tumor (odds ratio (OR): 8.359, [95% CI: 2.162-33.721], P = 0.002), CRKP isolation (OR: 7.766, [95% CI: 2.796-21.576], P = 0.001), chronic lung disease (OR: 5.020, [95% CI: 1.275-19.768], P = 0.020), and septic shock (OR: 4.591, [95% CI: 1.686-12.496], P = 0.003) were independent risk factors for the death of KP BSI. A 28-day mortality of KP BSI score ranging from 0 to 22 was developed based on the above 4 independent variables. Our scoring system revealed that the 28-day mortality were 9.14%, 35.29%, 38.10 %, 75% and 100% for carriers with a score of 0, 5, 6-10, 11-13 and ≥14, respectively. Additionally, CRKP infection were independently associated with intensive care unit stay (OR: 5.506, [95% CI: 2.258-13.424], P = 0.001), exposure to antifungals (OR: 4.679, [95% CI: 2.065-10.063], P = 0.001), exposure to fluoroquinolones (OR: 2.892, [95% CI: 1.151-7.267], P = 0.020), and the number of isolated bacterial species from the patient ≥ 3 (OR: 2.414, [95% CI: 1.306-4.463], P = 0.005). Conclusion: Our study may be useful for the reduction of the mortality of patients with KP BSI and the prevention of developing CRKP BSI in hospitals. Keywords: Bloodstream infections, Carbapenem resistance, Klebsiella pneumoniae, Risk factors, Mortality